Diabetes alters cardiorespiratory dynamics: insights from short-term recurrence quantification analysis of pulse-respiration quotient - Reyes-Lagos, José Javier; Guzmán-Ramos, Kioko; Lomelí, Joel; Pliego-Carrillo, Adriana Cristina; Peña-Castillo, Miguel Ángel; López-Sánchez, Pedro; Trujillo-Condes, Virgilio Eduardo; Garay-Jiménez, Laura Ivoone; Echeverría, Juan Carlos; Villegas-Zarco, María Fernanda; Santiago-Fuentes, Laura Mercedes (Frontiers in Physiology, 2025)
IntroductionThe Pulse-Respiration Quotient (PRQ) is considered a powerful tool for assessing dynamic interactions between cardiac and respiratory rhythms. Type 2 diabetes mellitus (T2DM) disrupts autonomic control, potentially compromising the complexity and adaptability of cardiorespiratory dynamics. In this cross-sectional, exploratory study, we investigated whether T2DM alters cardiorespiratory dynamics by analyzing short-term PRQ signals using conventional linear indices and Recurrence Quantification Analysis (RQA).MethodsThirty-eight participants (20 T2DM and 18 controls) completed four standardized tasks—supine rest, orthostatic challenge, paced breathing, and the Valsalva maneuver—while electrocardiographic and respiratory signals were continuously recorded. From these signals, R-to-R peak interval (RRI) and breath-to-breath (BB) time series were derived, allowing us to compute the PRQ time series as the ratio of instantaneous heart rate to instantaneous breathing rate. Linear indices of PRQ and RQA metrics were then calculated for the PRQ signals, enabling comparisons between groups (T2DM vs. control) and across tasks. Additionally, entropy-based mutual information (MI) between RRI and BB was assessed as a quantitative measure of cardiorespiratory coupling.ResultsT2DM participants exhibited higher recurrence rates and prolonged recurrence time of the first type in the PRQ series, especially during paced breathing, suggesting a more rigid and less adaptive control mechanism. Although linear PRQ indices showed changes in some stage-dependent responses, they were less adept than RQA metrics at discerning subtle differences between groups. Furthermore, the complementary cardiorespiratory coupling assessment by MI revealed distinct compensatory patterns in T2DM during paced respiration and Valsalva.ConclusionThese findings indicate potential dysautonomia or partial autonomic dysregulation in individuals with T2DM, as reflected by altered cardiorespiratory dynamics and reduced adaptability.